2019
DOI: 10.1186/s13578-019-0290-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA SNHG7 promotes pancreatic cancer proliferation through ID4 by sponging miR-342-3p

Abstract: Background: Small nucleolar RNA host gene 7 (SNHG7) is a novel identified oncogenic gene in tumorigenesis. However, the role that SNHG7 plays in pancreatic cancer (PC) remains unclear. In this study, we aimed to investigate the functional effects of SNHG7 on PC and the possible mechanism. Methods: The expression levels of SNHG7 in tissues and cell lines were measured by RT-qPCR. Cell viability, apoptosis, migration and invasion were examined to explore the function of SNHG7 on PC. Bioinformatics methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…Moreover, the present study revealed that miR-342-3p was a target miRNA of circSAMd4A. miR-342-3p has been demonstrated to be involved in cellular growth in cancers, including pancreatic cancer, hepatocellular carcinoma, prostate cancer and cervical cancer (35)(36)(37)(38). Zhang et al reported that miR-342-3p was downregulated in OS tissues and inhibited cell progression by targeting AEG-1 (39).…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the present study revealed that miR-342-3p was a target miRNA of circSAMd4A. miR-342-3p has been demonstrated to be involved in cellular growth in cancers, including pancreatic cancer, hepatocellular carcinoma, prostate cancer and cervical cancer (35)(36)(37)(38). Zhang et al reported that miR-342-3p was downregulated in OS tissues and inhibited cell progression by targeting AEG-1 (39).…”
Section: Discussionmentioning
confidence: 64%
“…Abnormal expression of snoRNA is a potential factor for carcinogenesis. It was reported that lncRNA-SNHG7 was able to affect the regulation of proliferation, metastasis and invasion and suppress apoptosis of malignant tumor cells including lung cancer (14), pancreatic cancer (15), esophageal cancer (16) and gastric cancer (17). However, its role in HCC has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG7 was upregulated in hepatocellular carcinoma and promoted cell metastasis process through blocking RBM5 expression. SNHG7‐miR‐342‐3p‐ID4 feedback loop has also been reported to accelerate tumor growth in vitro and in vivo in pancreatic cancer . Similarly, in the report by Li et al .…”
Section: Discussionmentioning
confidence: 61%